2021
DOI: 10.1259/bjr.20200437
|View full text |Cite
|
Sign up to set email alerts
|

Relative CT number of periappendiceal fat stranding may be an applicable index for estimating the severity of acute appendicitis

Abstract: Objectives: To investigate the feasibility of relative CT numbers to periappendiceal fat attenuation as an applicable index for estimating the severity of acute appendicitis. Methods: In total, 308 consecutive surgery-confirmed acute appendicitis patients and 243 controls with available preoperative CT were analyzed retrospectively. The radiological parameters were appendix diameter, length, and wall thickness as concurrent appendicitis signs. CT numbers of periappendiceal fat, mesenteric fat, subcutaneous fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Compared with prior models that also employed FS, our models were superior because they categorized FS into four grades (0–3). This grading system was also strongly supported by a recent study [ 44 ], which revealed attenuation of periappendiceal fat was significantly associated with the severity of appendicitis. Compared to patients with uncomplicated appendicitis, patients with complicated acute appendicitis exhibited higher CT number (or Hounsfield unit) of periappendiceal fat.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Compared with prior models that also employed FS, our models were superior because they categorized FS into four grades (0–3). This grading system was also strongly supported by a recent study [ 44 ], which revealed attenuation of periappendiceal fat was significantly associated with the severity of appendicitis. Compared to patients with uncomplicated appendicitis, patients with complicated acute appendicitis exhibited higher CT number (or Hounsfield unit) of periappendiceal fat.…”
Section: Discussionsupporting
confidence: 69%
“…Compared to patients with uncomplicated appendicitis, patients with complicated acute appendicitis exhibited higher CT number (or Hounsfield unit) of periappendiceal fat. [ 44 ] In our study, we assigned increasing scores in our new scoring system to different FS grades on the basis of their severity. Although model 4 developed by Kim et al [ 33 ] included FS as a predictor, they did not categorize FS into different grades.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study documented an average 6.3 days mean hospital stay in the ruptured group and only 2.9 days in non-perforated one 6 . Being non-invasive, Computed tomography (CT) scan has gained significant popularity in investigating AA, contrary to invasive approaches like diagnostic laparoscopy 7,8 . An earlier study recorded sensitivity and specificity of 69% and 97% respectively for CT scan in identifying ruptured appendicitis 9 .…”
Section: Introductionmentioning
confidence: 99%